Optimization of sowing time for adaptation to climate change and higher productivity of barley in the mid-Himalayas - Mahanta, Dibakar; Bisht, Jaideep Kumar; Kant, Lakshmi; Pattanayak, Arunava (Journal of Cereal Research, 2018)
Optimization of sowing date of barley was assessed by conducting three yearsâ€™ experiment with different sowing dates and three popular varieties of barley in the mid-Himalayas. With the help of quadratic equation, it was estimated that maximum grain yield of barley could be achieved with sowing on 12th November, which provided 8% higher yield compared to the existing recommended sowing date of 25th October. The present recommendation will help to adapt the climate change situation. Thousand-grain weight was the most important yield contributing attribute as found from the principal component analysis and correlation. Grain yield of barley could be modeled throughÂ the multi-linear regression equation with the help of yield attributes for the mid-Himalayas. The multi-linear regression equation will be highly useful for policymakers to estimate the yield of barley of either a district or a state in the mid-Himalayas. Â Doi.org/ 10.25174/2249-4065/2018/83644